Estimation of genetic parameters in cacao tree without raising progenies tests - Valois, Afonso Celso Candeira; Nascimento, José Carlos (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to estimate genetic parameters in Cacao tree (Theobroma cacao L.) with three years of age, using a hybrid population from IMC 67 x Catongo crosses. Estimates of variances, covariances, genetic and phenotypic correlations and the coefficient of heritability were obtained by using plant height and stem diameter characters. The coefficients of heritability, correlation and determination were high for plant height and low stem diameter. These results were compared with others from usual schemes, showing applicability of the method to cacao tree.